2004
DOI: 10.1002/jnr.20316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth factors on proliferation and phenotypic differentiation of human fetal neural stem cells

Abstract: Human fetal neural stem cells (hNSCs) can be expanded in vitro by mitogens or growth factors, such as basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), and/or leukemia inhibitory factor (LIF). Their effects on proliferation rate and differentiation pattern of hNSCs, however, have not been fully characterized. In this study, we cultured hNSCs in seven regimens, including bFGF, EGF, and LIF, either alone or in combinations. Cells were maintained as neurospheres in treatment media for various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 41 publications
7
73
0
Order By: Relevance
“…The differences in gene expression observed in these analyses do not appear strong enough to indicate that the spheres were generated as a result of contamination of cells from non-TM tissue, and could therefore reflect different levels of cell differentiation. The expression in HTM spheres of LIF, a gene involved in the maintenance of the undifferentiated state of embrionary stem cells (Pitman et al, 2004;Tarasenko et al, 2004), is consistent with this concept. HTM spheres also expressed nestin, which is considered a marker for neural precursor cells (Lendahl et al, 1990).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The differences in gene expression observed in these analyses do not appear strong enough to indicate that the spheres were generated as a result of contamination of cells from non-TM tissue, and could therefore reflect different levels of cell differentiation. The expression in HTM spheres of LIF, a gene involved in the maintenance of the undifferentiated state of embrionary stem cells (Pitman et al, 2004;Tarasenko et al, 2004), is consistent with this concept. HTM spheres also expressed nestin, which is considered a marker for neural precursor cells (Lendahl et al, 1990).…”
Section: Discussionsupporting
confidence: 65%
“…7). The selected genes included: Protein kinase (cAMP dependent) inhibitor beta (cluster 1), a gene involved in the maintenance of barrier function in vascular cells, (Lum et al, 2002); transgelin (cluster 2), a marker for smooth muscle cell differentiation (Owens et al, 2004); BDNF (cluster 2), believed to modulate neural progenitor cell proliferation and to enhance the maturation of neurons derived from EGF-generated neural stem cells (Schinstine and Iacovitti, 1997); IL-6 (cluster 3), known to act sinergistically with stem cell factors and required in vivo for the regulation of stem cells and committed progenitors of the hematopoietic system (Bernad et al, 1994); colony-stimulating factor 3 (cluster 3), involved in the mobilization of peripheral blood stem cells with long-term repopulating potential (Molineux et al, 1997); and leukemia inhibitory factor (LIF, cluster 3), which has been associated with the maintenance of the undifferentiated state of progenitor cells (Pitman et al, 2004;Tarasenko et al, 2004). We also confirmed in both floating spheres and normal HTM cells the expression of nestin considered a neural cell progenitor marker (Lendahl et al, 1990).…”
Section: Gene Expression Profile Analysismentioning
confidence: 99%
“…Cells were cultured as neurospheres and passaged every 10-11 days according to our previous description (Tarasenko et al, 2004). Growth media contained a basic medium supplemented with 20 ng/ml recombinant human epidermal growth factor (EGF) (R&D Systems, Minneapolis, MN), 20 ng/ml recombinant human basic fibroblast growth factor (bFGF) (R&D Systems), 5 μg/ml heparin (Sigma), and 10 ng/ml recombinant human leukemia inhibitory factor (LIF) (Chemicon, Temecula, CA).…”
Section: Cell Culturementioning
confidence: 99%
“…These cells proliferate in vitro in neurospheres, which consist of a heterogeneous population of neural stem cells and neural progenitors (Suslov et al, 2002). We have previously shown that mitogen-expanded and primed (Wu et al, 2002;Tarasenko et al, 2004) hNSCs become cholinergic motoneurons when grafted into acutely or chronically injured rat spinal cords (Gao et al, 2005;Tarasenko et al, 2007). However, grafted hNSCs showed limited survival rates and migrational capabilities within the injured cavity indicating the need for a scaffold support.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described. 66 Briefly, 5 or 50 lg of protein samples were probed with isoform and subunit specific primary antibodies (Santa Cruz Biotechnology, Inc., Santa Cruz, CA), including polyclonal goat anti-PP2B-Aa (PP2BA; 1:200), anti-PP2B-Ab (PP2BB; 1:200), anti-PP2B-B1 (CaNB1; 1:200), and anti-PP2B-B2 (CaNB2; 1:200). Blots were probed simultaneously with b-actin (1:20,000; Sigma-Aldrich, St. Louis, MO) as a loading control.…”
Section: Discussionmentioning
confidence: 99%